The Collaborative-Individual Learning in Improving the Critical Thinking Skills of Secondary Students in the Philippines - Viado, Ana Laigue; Department, Jo A. Espiritu (Future Science / FSH-PH Publications, 2023)
Critical thinking is at the forefront of learning, it builds self-empowerment and confidence. The study aimed to evaluate the influence of collaborative-individual learning on the critical thinking abilities of secondary students in the Philippines. The research sought to answer several questions, including the initial level of critical thinking skills, how the collaborative-individual learning approach was implemented, the level of critical thinking skills after the intervention, whether there was a significant difference before and after the intervention, and which group of students benefited the most from the approach. The study involved 215 Grade 10 students and utilized a single subject experimental design. Pre-tests and post-tests were conducted, and statistical tools such as item analysis, frequency distribution, mean difference, standard deviation, and t-tests were employed. The findings indicated that the students' critical thinking skills improved significantly after the application of collaborative-individual learning. School C demonstrated the highest level of interest and implementation. Based on the results, the study recommends incorporating collaborative-individual learning in teaching Economics and other subjects to enhance students' critical thinking skills. School administrators are encouraged to promote the use of this strategy.